ANALYSIS OF JUDGE'S DECISION CONSIDERATIONS ON THE ORIGIN OF CHILDREN FROM SIRRI MARRIAGES(CASE STUDY OF SOUTH JAKARTA RELIGIOUS COURT DECISION NUMBER: 650/PDT.P/2023/PA.JS) - Munawar, Sofyan Munawar; Munawar, Sofyan; Firdia; Nilman Ghofur (Almustofa Journal of Islamic Studies and Research, 2025)
Every child is a blessing and gift from the Supreme Creator, therefore children born out of wedlock should not be labeled as illegitimate, disgraceful, or damaging to reputation. There are 3 aspects of children's needs that parents are obligated to fulfill. The first part covers basic rights, which include providing a dignified identity, health protection, and ensuring security. The second part relates to custodial rights, namely providing breast milk nutrition, fulfilling living needs, instilling moral values, and other related matters. The third part concerns post-custody rights, which consist of personality development, socialization abilities, marriage, and various related aspects. Based on humanitarian aspects and child rights protection, religious courts have the authority to determine a child's origin to ensure the future welfare of children resulting from unregistered marriages or those born out of formal marriage. The research method adopts a normative qualitative approach, strengthened through primary and secondary data collection, while the data collection process utilizes observation, documentation, and interview techniques, followed by data validation through field checks and document verification to ensure validity. The research results reveal that 1) based on the Panel of Judges' decision, Petitioner I's status is declared as the biological father who has responsibilities, while government authorities have the power to impose ta'zir sanctions on parties causing the child's birth and 2) fulfillment of all aspects of the child's living needs includes providing financial support, access to education, health insurance, and various additional needs until the child reaches maturity and independence, including inheritance rights through mandatory will (wasiat wajibah) from the biological father's inheritance.